2017
DOI: 10.2355/isijinternational.isijint-2016-733
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafinegrained Microstructure in a Medium Manganese Steel after Warm Rolling without Intercritical Annealing

Abstract: Medium manganese steels are a grade of the third generation of advanced high strength steels (AHSS) that combine ductility, high strength and toughness for crashing resistance, determining characteristics for application in the automotive industry. During processing these steels are subjected to a hot and cold rolling followed by intercritical annealing in the field of austenite and ferrite phases. On the other side, the warm rolling processing is capable to reduce costs and operating time due to a single oper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 39 publications
5
21
0
Order By: Relevance
“…Inside the laths, some carbide precipitates were observed ( Figure 5d); presumably, these carbides can be of type Mn 23 C 6 or cementite according to Thermo-Calc predictions (Figure 1b). Recently, the former type was observed in 0.086%C-8.05%Mn-0.138%Si-0.0215%Al-Fe (wt.%) in the as-cast condition [19] and the latter has been reported to occur in GX12CrMoVNbN9-1 (GP91) cast steel [23]. When there is carbide precipitation in martensite laths, usually as small bars or plates morphologies, the phenomenon has been reported in the literature as auto-tempered martensite [24,25].…”
Section: Microstructural Characterization Of As-cast and Homogenized mentioning
confidence: 99%
See 1 more Smart Citation
“…Inside the laths, some carbide precipitates were observed ( Figure 5d); presumably, these carbides can be of type Mn 23 C 6 or cementite according to Thermo-Calc predictions (Figure 1b). Recently, the former type was observed in 0.086%C-8.05%Mn-0.138%Si-0.0215%Al-Fe (wt.%) in the as-cast condition [19] and the latter has been reported to occur in GX12CrMoVNbN9-1 (GP91) cast steel [23]. When there is carbide precipitation in martensite laths, usually as small bars or plates morphologies, the phenomenon has been reported in the literature as auto-tempered martensite [24,25].…”
Section: Microstructural Characterization Of As-cast and Homogenized mentioning
confidence: 99%
“…In this sense, it is essential to use simulated diagrams that allow for the study of the thermodynamic stability of the phases and their transformations, thus selecting the optimal route for heat treatment to achieve a given set of properties. Consequently, the simulated diagrams obtained through software such as Thermo-Calc ® and JMatPro ® have been widely used for this purpose [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of the application of intercritical rolling, i.e., WR at 650 °C after IA, to 0.1/0.2C‐5Mn steels showed that a further refined UFG ferrite and RA duplex microstructure and improved mechanical properties were gained . Similar results were also obtained in 0.08C‐8Mn steel subjected to WR at 630 °C without subsequent IA . A later investigation of HR 0.20C‐4.88Mn‐0.62Si‐3.11Al steel subjected to WR after IA at 750 °C revealed a UTS × TEL of ≈ 50 GPa · %, which was almost independent of WR thickness reduction, was obtained…”
Section: Introductionmentioning
confidence: 99%
“…HR or HR plus cold rolling (CR) and subsequent IA treatment are commonly applied to produce medium Mn steel sheets . More recently, the application of the WR technique to medium Mn steel has gained increasing attention mainly for the purpose of further improving its mechanical properties and/or simplifying and accelerating conventional production processes . Early studies of the application of intercritical rolling, i.e., WR at 650 °C after IA, to 0.1/0.2C‐5Mn steels showed that a further refined UFG ferrite and RA duplex microstructure and improved mechanical properties were gained .…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] As such, hot forming and warm forming techniques have recently regained popularity. 11) The hot forming has been studied in our previous study. 12) Recently, several warm forming studies focused on the dynamic recrystallization (DRX) and dynamic recovery (DRV) of ferrite and austenite during warm deformation process.…”
Section: Introductionmentioning
confidence: 99%